2016
DOI: 10.1176/appi.ps.201500347
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Emergency Department Use by Individuals With Bipolar Disorder Enrolled in a Collaborative Care Implementation Study

Abstract: Objectives The study assessed correlates of emergency department use among individuals with bipolar disorder receiving a collaborative care program. Methods Community-based clinics from two states implemented the evidence-based Life Goals-Collaborative Care Model (LG-CC), which included self-management sessions and care management contacts. Logistic regression analysis was used to determine participant factors associated with 12-month emergency department use after LG-CC implementation. Results Among 219 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Lack of change in acute care use contrasts a previous study that found an association between increased contact with care management and increased ED visits. 24 Furthermore, our study found that higher clinic PC-MHI engagement had a small, nonsignificant reduction in total cost of care, in some contrast with other studies demonstrating modest additional costs but overall cost effectiveness of collaborative care in other settings. 25,26 To fully understand the financial burden of these services and whether they can be deemed as high value care, however, requires a more comprehensive cost-analysis that includes program implementation and operation costs.…”
Section: Discussioncontrasting
confidence: 78%
“…Lack of change in acute care use contrasts a previous study that found an association between increased contact with care management and increased ED visits. 24 Furthermore, our study found that higher clinic PC-MHI engagement had a small, nonsignificant reduction in total cost of care, in some contrast with other studies demonstrating modest additional costs but overall cost effectiveness of collaborative care in other settings. 25,26 To fully understand the financial burden of these services and whether they can be deemed as high value care, however, requires a more comprehensive cost-analysis that includes program implementation and operation costs.…”
Section: Discussioncontrasting
confidence: 78%